Respuesta :

Answer:

x = 7.

Step-by-step explanation:

-18 = 6 (x - 10)

-18 = 6x - 60

6x = -18 + 60

6x = 42

x = 42/6 = 7.

Answer:

[tex]x=7[/tex]

Step-by-step explanation:

[tex]-18=6(x-10)[/tex]

Use distributive property.

[tex]-18=6x-60[/tex]

Add 60 on both sides.

[tex]-18+60=6x[/tex]

[tex]42=6x[/tex]

Divide by 6 on both sides.

[tex]\frac{42}{6} =x[/tex]

[tex]7=x[/tex]

Another method.

[tex]-18=6(x-10)[/tex]

Divide by 6 on both sides.

[tex]-18/6=x-10[/tex]

[tex]-3=x-10[/tex]

Add 10 on both sides.

[tex]-3+10=x[/tex]

[tex]7=x[/tex]

Give me Brainliest if my answer helped you.

ACCESS MORE